Ethnic Fashion - Gardetti, Miguel Angel; Muthu, Subramanian Senthilkannan (Environmental Footprints and Eco-design of Products and Processes,, 2016)
This is the first book to introduce readers to the crux of ethnic fashion. Covering all aspects, it addresses the significance of sustainability (including culture) and ethnic fashion in the apparel industry. It also highlights concepts and case studies pertaining to ethnic fashion.